THE IMPLEMENTATION OF BLENDED LEARNING METHOD IN ENGLISH LANGUAGE TEACHING (Karya Ilmiah Mahasiswa (KIMA), 2024)
The goal of this research is to find out what eleven A1-grade senior high school students in Darul Aman Gombara Makassar thought about the introduction of the blended learning method in English language teaching and what the method's benefits were for the students. This study used a descriptive technique that took one month to collect data using a closed-ended questionnaire, an open-ended questionnaire, and an interview. Purposive sampling was used to collect data from the class of eleven A1 classes, which included 35 students. To determine the students' perceptions, the closed-ended questionnaire scores were converted into percentages and examined. The results of the open-ended questionnaire and interview were incorporated into the description. The findings of this study are revealing that students had a favorable attitude about the use of the Blended Learning Method in English Language Teaching. The respondents' positive judgment stemmed from their experience studying utilizing the Blended studying Method.